An Enhanced Bio-Inspired Aco Model For Fault-Tolerant Networks - Samuel Lusweti; Collins Odoyo; Dorothy Rambim (Information System; Universitas Buana Perjuangan Karawang, 2023)
This research mainly aimed at establishing the current functionality of computer network systems, evaluating the causes of network faults, and developing an enhanced model based on the existing ACO model to help solve these network issues. The new model developed suggests ways of solving packet looping and traffic problems in common networks that use standard switches. The researcher used simulation as a method of carrying out this research whereby an enhanced algorithm was developed and used to monitor and control the flow of packets over the computer network. The researcher used an experimental research design that involved the development of a computer model and collecting data from the model. The traffic of packets was monitored by the Cisco Packet Tracer tool in which a network of four computers was created and used to simulate a real network system. Data collected from the simulated network was analyzed using the ping tool, observation of the movement of packets in the network and message delivery status displayed by the Cisco Packet Tracer. In the experiment, a control was used to show the behavior of the network in ideal conditions without varying any parameters. Here, all the packets sent were completely and correctly received. Secondly, when a loop was introduced in the network it was found that the network was adversely affected because for all packets sent by the computers on the network, none of them was delivered due to stagnation of packets. In the third experiment, still, with the loops on, a new ACO model was introduced in the cisco packet tracer used to simulate the network. In this experiment, all the packets sent were completely and correctly delivered just like in the control experiment.